2020
DOI: 10.1002/rcm.8790
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic fractionation during acid digestion of calcite: A combined ab initio quantum chemical simulation and experimental study

Abstract: Rationale:Carbonate clumped isotope analysis involves the reaction of carbonate minerals with phosphoric acid to release CO 2 for measurement in a gas-source isotope ratio mass spectrometer. Although the clumped isotope proxy is based on the temperature dependence of 13 C-18 O bonding preference in the mineral lattice, which is captured in the product CO 2 , there is limited information on the phosphoric acid reaction mechanism and the magnitude of clumped isotopic fractionation (mass 63 in CO 3 2− to mass 47 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 75 publications
(152 reference statements)
1
21
0
Order By: Relevance
“…Starting with a dolomite dimer (Figure 1A), the reaction mechanism at the mineral–acid interface is modeled. We propose a mechanism where the acid digestion reaction commences with protonation of the carbonate dimer 17,18 . The proton is produced by deprotonation of the acid in the presence of water.…”
Section: Theory and Computationmentioning
confidence: 99%
See 4 more Smart Citations
“…Starting with a dolomite dimer (Figure 1A), the reaction mechanism at the mineral–acid interface is modeled. We propose a mechanism where the acid digestion reaction commences with protonation of the carbonate dimer 17,18 . The proton is produced by deprotonation of the acid in the presence of water.…”
Section: Theory and Computationmentioning
confidence: 99%
“…The reaction scheme for 2a is shown in Figure 2 and the QST3 calculation is based on this particular reaction step of the acid digestion reaction. It was shown that the first protonation on the bridging oxygen of the carbonate dimer releases product CO 2 19 and this is the deciding step of the type of the fractionation that follows 17 (Equation ). After the first protonation, the protonated oxygen atom remains attached to the cations of the dolomite dimer (Figure 2).…”
Section: Theory and Computationmentioning
confidence: 99%
See 3 more Smart Citations